The Efficacy of Nerve Growth Factor Antibody for the Treatment of Osteoarthritis Pain and Chronic Low-Back Pain: A Meta-Analysis - Yang, Si; Huang, Yu; Ye, Ziqi; Li, Lu; Zhang, Yu (Frontiers in Pharmacology, 2020)
Abstract Background: Nerve growth factor (NGF) plays a crucial role in pain modulation, it is considered as a new therapeutic target for pain therapy. The purpose of this meta-analysis was to study the efficacy of anti-NGF antibody for the treatment of osteoarthritis pain and chronic low-back pain and to provide evidence and hints for further research and practice. Methods: PubMed, Embase, Wanfang Data, and China National Knowledge Infrastructure (CNKI) were searched from inception to November 30, 2019. Eligible studies should include randomized clinical trials-based investigations of anti-NGF antibody treatment for osteoarthritis pain and chronic low-back pain. Pooled overall mean changes from baseline to check point in the Western Ontario and McMaster Universities Arthritis Index (WOMAC) measures of pain, physical function and Patient’s Global Assessment (PGA) were calculated with either a fixed-effects model or a random-effects model depending on the tests for heterogeneity. Sensitivity analysis and bias of publication were assessed. Results: A total of 7 studies (3890 patients) were included in this meta-analysis. The pooled analysis showed statistically significant reduction in the WOMAC pain (standardized mean difference (SMD) = -2.22, 95% confidence interval (CI) = -3.44 to -0.99, Z = -3.55, P = 0.0004; I2 = 99%), the WOMAC Physical Function (SMD = -2.76, 95% CI = -4.22 to -1.30, Z = -3.71, P = 0.0002; I2 = 99%), and the PGA Index (SMD = -2.76, 95% CI = -4.42 to -1.09, Z = -3.24, P = 0.0012; I2 = 99%), respectively. Pooled difference of adverse events rates in experimental and control groups was 0.11 (95% CI = 0.02 to 0.20, Z = 2.41, P = 0.016; I2 = 83%). Conclusion: Our meta-analysis data indicate that anti-NGF antibody can relive pain and improve function in patients with osteoarthritis pain and chronic low-back pain. Keywords: anti-NGF antibody, osteoarthritis pain, chronic low-back pain, immunological treatment, meta-analysis